Ինքնության պահպանման խնդիրը Միգրացիայի դարաշրջանում - Սողոմոնյան, Ամալյա (Արմավ հրատ.)
The topic of deportation has always been and will always be in the world literature. The eras are changing, so are the literary themes, new realities are emerging, but, unfortunately, there are always reasons why a person is forced to emigrate. Evidence of this is the last Artsakh war, which after some time will be reflected in fiction. The purpose of the article is to show the influence of various factors (including war) on an individual’s psychology and the desire to emigrate. In literary works, the authors do everything so that love wins, but in real life, the opposite happens. Explosions, abandoned houses, memories and an uncertain future. Loss of ideals, disappointment, alienation. War destroys everything. After the war, the individual is spiritually and morally abandoned, defenseless, without hopes and goals. During the war, the most important thing dies - love. After the war, the individual has feelings of alienation, self-alienation, self-destruction. Unfortunately, emigration often comes to the rescue of the individual. In conclusion, it should be noted that it is impossible to talk about modern literature without touching the topics of globalization and migration. To understand how the migrant feels, one must at least once feel the real danger of losing home, be displaced, live with the fate of a migrant, lose homeland and go into uncertainty. Тема депортации всегда была и будет в мировой литературе. Меняются эпохи, меняются и литературные темы, возникают новые реалии, но, к сожалению, всегда есть причины, по которым человек вынужден эмигрировать. Свидетельство тому – последняя война в Арцахе, которая через некоторое время найдет свое художественное отражение в литературе. Цель данной статьи - показать влияние различных факторов (в том числе войны) на психологию индивида и желание эмигрировать. В литературных произведениях авторы делают все, чтобы любовь победила, а в реальной жизни все происходит наоборот. Взрывы, заброшенные дома, воспоминания и неопределенное будущее. Потеря идеалов, разочарование, отчуждение. Война уничтожает все. После войны личность духовно и нравственно покинута, беззащитна, она остается без надежд и целей. На войне умирает самое главное - любовь. После войны личность испытывает чувства отчуждения, самоотчуждения, саморазрушения. К сожалению, эмиграция часто приходит на помощь личности. В заключение можно сказать, что невозможно говорить о современной литературе, не затрагивая темы глобализации и миграции. Чтобы понять, что чувствует мигрант, нужно хотя бы раз ощутить реальную опасность потерять свой дом, быть перемещенным, смириться с судьбой мигранта, потерять землю, родину и уйти в неизвестность.
Keywords: Արտասահմանյան գրականություն; Միգրացիա